Architektur und Städtebau im geteilten Polen des 19. Jahrhunderts im politischen Kontext - Zabłocka-Kos, Agnieszka (Artium Quaestiones, 2018)
The essay, focusing on architecture in the nineteenth-century partitioned Poland, is an attempt to read its meanings in the context of the colonial policies of Russia, Prussia, and the Austro-Hungarian Empire. The analyzed material includes selected buildings and city centers of Poznań, Warsaw, and Cracow, while the problems addressed are the encoding of urban space meanings and its deciphering in the context of complex nineteenth-century Polish history.